Compreensão de textos escritos: um estudo de caso em turmas de 5º ano - Costa, Jane Pereira (2011)
This work presents a research whose objective was to investigate to what extent students from the 5th grade of elementary school comprehend texts adequate to their age range. The research was carried out during the years of 2009 and 2010, in a municipal public school in Maceió, State of Alagoas, Brazil, and involved 3 groups of students of the 5th grade, totalizing 90 students. The methodology adopted was experimental and can be characterized as a case study, with a quantitative approach and also with a qualitative analysis of the data. The instruments used to collect data were four cloze tests, two multiple choice tests, interviews with twenty students and a questionnaire for the three teacher-collaborators. The theoretical foundation was based on a sociocognitive and interactional approach of reading, whose assumptions are defended by several authors, among them can be cited the following researchers: Kato (1995), Kleiman (2002, 2003, 2004); Leffa (1996), Lencastre (2003), Trevisan (1992), Marcuschi (2002) and Silveira (2005). In relation to the cloze test, the author searched for Santos et al.(2009); and in respect to the multiple choice test, she used the rationale of Prova Brasil, a national reading exam. The results of the research pointed to an oscillation of the comprehension of written texts among the students. In fact, the results of the multiple choice tests were better than the ones resulting from the cloze tests. In this sense, the influence of intervenient variables, such as the proceedings used, textual typology and textual genre must be considered. The results also indicated that there is a need for the adoption of a more effective reading practice in the classroom, considering the existence of students who have serious difficulties in reading and a few others who are not literate. Finally, the results of the research pondered that a reading program mostly based on the top down process does not empower those students who do not master the bottom up process with proficiency.